Epidemiological study of congenital malformations at birth in a tertiary health centre in central India - Naik, Manuja; Bhargava, Meena; Yadav, Kalpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The proposed study was carried out to determine incidence of congenital malformations, incidence of CM in live and still births, risk factors attributable, maternal and perinatal outcome, to frame the recommendations for early detection and prevention of CM. Methods: Prospective observational study. The cases selected from those attending the antenatal O.P.D. and those admitted in wards of Obs and Gynae Dept., GMH who delivered congenitally malformed baby dated from August 2013-July 2014. A detailed history, examination, relevant investigations was done. Results: Out of 9014 deliveries, 110 babies had CM. The incidence of CMs was found to be 1.22%. Maximum number (24.55%) of CM s were of CNS, most common was NTD (Anencephaly). Incidence of CMs was more in still births, mothers of age >40 yrs and <20 yrs, of illiterate, educated <8 std., house wives, rural areas, unbooked and multigravida. Most CM fetuses were delivered prematurely (67.27%). CVS and CNS systems were more commonly involved in consanguinous married couples. CM was associated with drug intake, 1.82% on antiepileptics, 1.82% on antihypertensives, 3.64% on oral hypoglycaemics,0.91% on NSAID,6.36% on unspecified drugs. 12.73% CMs were seen in passive smokers, 6.36% consumed alcohol, 17.27% pan/gutka intake. Majority were delivered by vaginal route, maximum fetuses (82.73%) were in vertex presentation, maximum (67.27%) CMs were in male babies. Conclusions: Many malformations arise because of the interplay of genetic, environmental and multifactorial factors. The stress imposed may be reduced considerably by understanding the causes of the malformations and adopting the management strategies outlined for the prevention or reduction of CM.